Determination of Total Phenolic, Flavonoid, and DPPH Scavenging Activity of Ruku-ruku (Ocimum tenuiflorum L.) Leaf - Fadhli, Haiyul; Islami, Rizzati; Utami, Rahayu; Dona, Rahma (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2024)
Ruku-ruku (Ocimum tenuiflorum L.) is a plant that contains essential oils as well as phenolic and flavonoid compounds that act as antioxidants. This study aims to determine the total phenolic (TPC) and flavonoid content (TFC) and the DPPH scavenging activity of ruku-ruku leaves. Ruku-ruku leaf extraction was carried out using the maceration method using methanol. Measurement of TPC by Folin Ciocalteu method, TFC by AlCl3 complex formation method, and antioxidant activity by DPPH method. The test results using a microplate reader showed that the methanol extract of ruku-ruku leaves had a total phenolic content of 300.71±2.86 mgGAE/g extract and total flavonoid content of 66.42±10.17 mgQE/g extract as well as very weak antioxidant activity (IC50 = 2501.07±1.2 µg/mL).